2013
DOI: 10.1002/ange.201301328
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed ortho Acylation of Aromatic Carboxylic Acids

Abstract: Neue Richtung: Die Carboxygruppe von Benzoesäuren steuert deren ortho‐Acylierung mit Carbonsäureanhydrid in Gegenwart eines Rhodiumkatalysators (siehe Schema; cod=Cyclo‐1,5‐octadien). Diese ortho‐Acylierung bildet eine Ergänzung zu der meta‐Selektivität von Friedel‐Crafts‐Reaktionen. Die Produkte können durch Protodecarboxylierung in Arylketone überführt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…In the context of our research on catalytic reactions starting from benzoic acid substrates,20 we have developed a Rh‐catalyzed ortho ‐acylation of benzoic acids 16h. While optimizing the reaction conditions, we had occasionally detected trace quantities of 3‐alkylidenephthalides ( 3 ), and reasoned that they must have formed by acylalization and consecutive elimination of the cyclized isomer ( 4′ ) of the 2‐acylbenzoic acid products, as illustrated in the Scheme in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of our research on catalytic reactions starting from benzoic acid substrates,20 we have developed a Rh‐catalyzed ortho ‐acylation of benzoic acids 16h. While optimizing the reaction conditions, we had occasionally detected trace quantities of 3‐alkylidenephthalides ( 3 ), and reasoned that they must have formed by acylalization and consecutive elimination of the cyclized isomer ( 4′ ) of the 2‐acylbenzoic acid products, as illustrated in the Scheme in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…During the preparation of the review, the Gooßen group reported the ortho ‐acylation of benzoic acids to form o ‐acyl benzoic acids, Scheme C1,2 and 3‐alkylidenephthalides, Scheme C2 3.…”
mentioning
confidence: 99%
“…This type of oxidative coupling reaction catalyzed by palladium has provided important innovations for synthetic chemistry over the past decades . Recently, similar reactions of oxidative annulation or decarboxylation by rhodium or ruthenium catalysis have been reported by Ackermann, Miura, Jeganmohan, and Rovis et al since 2007. , These reactions have greatly supplemented the study of oxidative C–H bond transformations proceeding via C–H/O–H or C–H/N–H bond cleavages, which provide an atom-economical way to synthesize α-pyrones and pyridines. But oxidative annulations between internal alkynes and acrylic acid or amide by palladium catalysis are still a big challenge, because of the relatively less catalytic activity and the different reaction mechanism.…”
mentioning
confidence: 90%